Diabetes Worsens Skeletal Muscle Mitochondrial Function, Oxidative Stress, and Apoptosis After Lower-Limb Ischemia-Reperfusion: Implication of the RISK and SAFE Pathways? - Pottecher, Julien; Adamopoulos, Chris; Lejay, Anne; Bouitbir, Jamal; Charles, Anne-Laure; Meyer, Alain; Singer, Mervyn; Wolff, Valerie; Diemunsch, Pierre; Laverny, Gilles; Metzger, Daniel; Geny, Bernard (Frontiers in Physiology, 2018)
OBJECTIVES: Diabetic patients respond poorly to revascularization for peripheral arterial disease (PAD) but the underlying mechanisms are not well understood. We aimed to determine whether diabetes worsens ischemia-reperfusion (IR)-induced muscle dysfunction and the involvement of endogenous protective kinases in this process. MATERIALS AND METHODS: Streptozotocin-induced diabetic and non-diabetic rats were randomized to control or to IR injury (3h of aortic cross-clamping and 2h of reperfusion). Mitochondrial respiration, reactive oxygen species (ROS) production, protein levels of superoxide dismutase (SOD2) and endogenous protective kinases (RISK and SAFE pathways) were investigated in rat gastrocnemius, together with upstream (GSK-3β) and downstream (cleaved caspase-3) effectors of apoptosis. RESULTS: Although already impaired when compared to non-diabetic controls at baseline, the decline in mitochondrial respiration after IR was more severe in diabetic rats. In diabetic animals, IR-triggered oxidative stress (increased ROS production and reduced SOD2 levels) and effectors of apoptosis (reduced GSK-3β inactivation and higher cleaved caspase-3 levels) were increased to a higher level than in the non-diabetics. IR had no effect on the RISK pathway in non-diabetics and diabetic rats, but increased STAT 3 only in the latter. CONCLUSION: Type 1 diabetes worsens IR-induced skeletal muscle injury, endogenous protective pathways not being efficiently stimulated.